TRADE COOPERATION AND AUSTRIAN INVESTMENT ACTIVITY IN UKRAINE - Safarians, Yevhenii (Torun International Studies, 2016)
The article deals with problem of trade cooperation and Austrian investment activity in Ukraine over the past 25 years. The purpose of the paper was to find the reasons of interest in Ukraine by Austrian government and financial circles. Data for this study was collected from international documents and diplomatic statements of Austria and Ukraine. The study shows that Austrian investment activity in Ukraine has some good perspectives.